Penile Prosthesis: What Should We Do about Complications?. (4th November 2008) - Bettocchi, C.; Ditonno, P.; Palumbo, F.; Lucarelli, G.; Garaffa, G.; Giammusso, B.; Battaglia, M.
Abstract : Even in the era of phoshodiesterase type 5 inhibitors, penile implants are considered the definitive solution for the treatment of organic erectile disfunction. The advent of new surgical tools and new infection-resistant materials has significantly reduced the risk of intra and post-operative complications and the need for revision surgery. Various companies have also improved their mechanical systems in order to reduce the risk of failures, and their products are now so good they may last lifelong. In this article, we evaluate the intraoperative and postoperative complications recorded in our experience and in literature reports, and make some suggestions as to how to prevent or correct them.